Integration of Creative Economy and Tourism in the Development of Colorful Villages Implications for the Economy of Malang's Big Market - Dipo Piswatama; Sri Yunita; Jamaludin Jamaludin; Oksari Anastasya Sihaloho (FKIP, Universitas Palangka Raya, 2024)
This research is entitled Integration of the Creative Economy and Tourism in the Development of Colorful Villages. Implications for the Economy of the Malang Large Market. The author is interested in the title of this research, because the colorful village of Jodipan is the most popular destination in the city of Malang and whether the impact of the Malang big market on decreasing its economy is due to the existence of the colorful village of Jodipan. In this research, the author uses a qualitative method in the form of interviews because the two places in Malang City are the economic center of Malang City, whether these two places are mutually beneficial or detrimental. The solution for the writer is that the large Malang market sells international goods and the colorful village of Jodipan sells basic necessities so that each other can benefit and not harm each other. This research concludes that two places have different values ​​and the author believes that the existence of two places in the city of Malang will improve the economy in the city of Malang to become the largest center in Indonesia.